Fireproof corrosion-resistant water-based paint and preparation method thereof
By combining the silicon sol composite polyacrylate emulsion with a crosslinker containing bidynamic imine bonds, a dense three-dimensional network structure is formed, which solves the problems of traditional water-based coatings being easily eroded, insufficient fire resistance and lack of self-repair in harsh environments, and achieves water-based coatings with high corrosion resistance, fire resistance and self-repair capabilities.
Patent Information
- Application Number
- CN202411887122.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional water-based coatings are prone to erosion in harsh chemical environments, have insufficient fire resistance and lack self-repair capabilities, resulting in coating failure and shortened service life.
By combining the silica sol composite polyacrylate emulsion with a crosslinking agent containing a bidynamic imine bond, a fire-resistant and corrosion-resistant water-based coating is formed. The coating forms a dense three-dimensional network structure during the film formation process, improving the corrosion resistance and fire resistance of the coating, and giving it a self-healing function.
It significantly improves the corrosion resistance and fire resistance of the coating, realizes self-healing capabilities, and enables the coating to partially restore its original performance after being damaged by external forces, extending its service life.
Smart Images

Figure BDA0005199633230000111 
Figure BDA0005199633230000121 
Figure BDA0005199633230000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, in particular to a fire-proof and corrosion-resistant water-based coating and a preparation method thereof. Background Art
[0002] In the modern coatings industry, water-based coatings have attracted much attention because they use water as a dispersion medium and have environmentally friendly characteristics such as low volatile organic compound (VOC) emissions. Water-based coatings are widely used in many fields such as construction, automobiles, furniture, and industrial protection. In the construction field, they can be used for interior and exterior wall decoration to provide beauty and protection; in the automotive industry, they are used for body painting to ensure appearance and resist external erosion; in furniture, they can give the surface a good texture and protective effect; in industrial protection, they can provide anti-corrosion, wear-resistant and other protective effects for various equipment and facilities. However, traditional water-based coatings often face problems such as insufficient corrosion resistance, easy erosion in harsh chemical environments, resulting in coating failure; poor fire resistance, unable to effectively prevent the spread of flames in fire-hazardous scenarios; and lack of self-repairing ability. Once damaged by external forces to form cracks or scratches, they cannot recover on their own, reducing the protective effect and service life of the coating. The self-healing corrosion-resistant and fire-retardant water-based coating of the present invention aims to solve these pain points. Through a unique combination of components and synergistic effects, it integrates silica sol composite polyacrylate emulsion, a cross-linking agent containing a double dynamic imine bond, etc., and is committed to giving the coating a self-healing function while improving corrosion resistance and fire resistance, so as to meet the growing demand for high-performance, long-life, and environmentally friendly coatings in various fields. Summary of the invention
[0003] The purpose of the present invention is to provide a fire-proof and corrosion-resistant water-based coating and a preparation method thereof, so as to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a fire-resistant and corrosion-resistant water-based coating and a preparation method thereof, characterized in that the preparation steps are as follows:
[0005] (1) preparing an emulsifier solution;
[0006] (2) taking methyl methacrylate, 2-ethyl acrylate, butyl acrylate, acrylic acid, and acrylonitrile in proportion and mixing them uniformly to obtain a mixed monomer;
[0007] (3) adding a pH buffer into a container, adding the emulsifier solution obtained in step (1) and the mixed monomer obtained in step (2), stirring evenly to obtain a pre-emulsified liquid, heating, adding dropwise an initiator solution, and adjusting the pH after the reaction is complete to obtain a polyacrylate emulsion;
[0008] (4) taking the epoxy resin emulsion, mixing it with the polyacrylate emulsion obtained in step (3), stirring it, and performing a degassing treatment to obtain an epoxy resin modified polyacrylate emulsion;
[0009] (5) Weighing ethyl orthosilicate and ethanol in a container according to the mass ratio, stirring, adding deionized water to dissolve, keeping the temperature in a water bath, adding a catalyst and an organic silane coupling agent, continuously stirring and mixing, condensing and refluxing, and obtaining a uniform silica sol;
[0010] (6) adding nano magnesium hydroxide to the nano silica sol obtained in step (5), stirring and dispersing, to obtain nano magnesium hydroxide modified silica sol;
[0011] (7) adding the polyacrylate emulsion obtained in step (3) and the nano-magnesium hydroxide-modified silica sol obtained in step (6) into a container, adding a crosslinking agent, heating and stirring, continuing to add an emulsifier, a defoaming agent, and a thickener, and mixing evenly to obtain a fire-resistant and corrosion-resistant water-based coating;
[0012] The cross-linking agent is prepared by the following method:
[0013] (i) taking o-hydroxybenzaldehyde and an alcohol compound into a container, adding an organic solvent to dissolve, adding a catalyst and a water absorbent, mixing evenly, and reacting to obtain an intermediate;
[0014] (ii) mixing the intermediate obtained in step (i) with p-phenylenediamine to react to obtain a cross-linking agent containing a dual dynamic imine bond;
[0015] The molar mass ratio of o-hydroxybenzaldehyde, alcohol compound, catalyst and water absorbent in step (i) is 1.1-1.8:1.1-1.5:0.4-0.6:1.5-2.5; the molar mass ratio of intermediate and p-phenylenediamine in step (ii) is 0.25-0.6:1-1.2.
[0016] Furthermore, the emulsifier in step (1) is sodium dodecyl sulfate and nonylphenol polyoxyethylene ether, and the mass ratio thereof is 1:1.5-2.
[0017] Furthermore, in the step (2), the mass ratio of methyl methacrylate, 2-ethyl acrylate, butyl acrylate, acrylic acid and acrylonitrile is 180-220:80-100:90-110:8-12:25-35.
[0018] Furthermore, the pH buffer in step (3) is sodium bicarbonate, the mass of which is 0.1-0.5% of the total monomer mass in step (2); and the initiator is ammonium persulfate, the mass of which is 0.2-1% of the total monomer mass in step (2).
[0019] Furthermore, the epoxy resin emulsion in step (4) is a bisphenol A epoxy resin emulsion with an epoxy equivalent of 180 to 190 g / eq; the epoxy resin emulsion is obtained by reacting bisphenol A epoxy resin, a hydrophilic monomer, an initiator and an emulsifier.
[0020] Furthermore, a fire-retardant and corrosion-resistant water-based coating is provided, characterized in that the fire-retardant and corrosion-resistant water-based coating comprises the following components in terms of components: 100-150 parts of polyacrylate emulsion, 60-100 parts of epoxy resin emulsion, 30-50 parts of silica sol, 10-25 parts of nano magnesium hydroxide, 6-15 parts of cross-linking agent, 0.3-2 parts of emulsifier, 0.5-2 parts of thickener and 0.1-0.3 parts of defoaming agent; the coating is prepared by the method.
[0021] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0022] The present invention uses epoxy resin modified polyacrylate emulsion as film-forming emulsion. The polyacrylate emulsion contains a molecular chain structure formed by polymerization of acrylic ester monomers, which gives the coating good flexibility and initial adhesion. The ester group and other groups on the molecular chain help maintain the basic physical properties of the coating. The epoxy resin is used for modification, and the epoxy group reacts with the curing agent to form an interpenetrating network structure with the polyacrylate emulsion, thereby improving the compactness of the coating. The epoxy group and the benzene ring structure can effectively resist the erosion of corrosive media such as acids and alkalis, and prevent the penetration of corrosive ions by forming a dense protective layer, thereby improving the corrosion resistance of the coating. In terms of fireproof performance, the epoxy resin decomposes to form a carbon layer, which synergistically acts with the composite nano magnesium hydroxide modified silica sol, the carbon layer blocks heat and oxygen transmission, and the hydroxide decomposes and absorbs heat when heated to produce magnesium oxide, thereby further preventing flame retardancy.
[0023] The present invention uses magnesium hydroxide modified silica sol and epoxy resin modified polyacrylate emulsion as film-forming materials. When the coating is film-formed, polymer molecules in the polyacrylate emulsion gradually form a continuous film structure through the entanglement and interaction of molecular chains. The silica particles in the silica sol are evenly dispersed in the emulsion system. As the drying and forming process proceeds, the silica particles gradually aggregate and fill the gaps between the polyacrylate molecular chains. The surface silanol groups interact with the active groups of the polyacrylic acid molecular chains and are connected through hydrogen bonds or silicon-oxygen bonds. The synergistic effect forms a dense and uniform three-dimensional network structure, thereby improving the physical properties of the coating. The drying speed of the polyacrylate emulsion is affected by its own chemical composition and environmental factors. It also takes a certain amount of time for the water in the silica sol to evaporate. In addition, the interaction between the silica sol and the polyacrylate during the evaporation process affects the diffusion path of the water. The silica sol is used for compounding, thereby reducing the problem of surface defects caused by too fast film formation, thereby making the film formation uniform and stable. The silica particles in the silica sol form a physical barrier in the coating to prevent the penetration of water molecules. The silicon-oxygen-silicon bonds formed between the silanol groups and the connecting bonds between the polyacrylate molecules enhance the overall water resistance of the coating.
[0024] The present invention uses a cross-linking agent containing a double dynamic imine bond, which undergoes a cross-linking reaction with the active groups on the polyacrylate molecular chain to form a more stable and complex three-dimensional network structure, thereby enhancing the integrity and density of the coating. At the same time, when the coating is damaged by external force, the imine bond breaks, and the molecular chains around the damaged area can be rearranged and cross-linked under certain conditions to achieve self-repair. The flexibility and fluidity of the polyacrylate emulsion provide a basis for the rearrangement of the molecular chains, while the rigid structure of the silica sol helps to maintain the shape and stability after repair, so that the repaired coating can be restored to performance close to the original state, thereby improving the service life and sustainability of the coating. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the fire-resistant and corrosion-resistant water-based coatings prepared in the following examples are as follows:
[0027] Salt spray resistance: Use 150mm×75mm×3mm steel plate, paint film thickness 6mm, test according to ASTM B117 standard;
[0028] Fire resistance: Use a steel plate of 150mm×150mm×6mm and a paint film thickness of 6mm. Test according to GA / T714-2007 standard. The time when the back temperature of the steel plate reaches 450℃ is taken as the fire resistance limit.
[0029] Carbon layer strength: Cut and select a carbon layer of 45mm×45mm from the carbon layer after the fire resistance test, use a compression bending tester to test it at a downward pressure speed of 5mm / min, and record the strength value;
[0030] Corrosion rate: Use a steel plate of 150mm×150mm×6mm, with a paint film thickness of 6mm, and use the GB / T19746-2005 method for testing, taking the average of three times;
[0031] Drying time: JG / T 335-2011
[0032] Example 1
[0033] (1) adding 0.35 parts of sodium lauryl sulfate and 0.55 parts of nonylphenol polyoxyethylene ether into a container, dissolving them with deionized water, and stirring them uniformly to obtain an emulsifier solution;
[0034] (2) taking 200 parts of methyl methacrylate, 90 parts of 2-ethyl acrylate, 100 parts of butyl acrylate, 10 parts of acrylic acid, and 30 parts of acrylonitrile in a container and mixing them uniformly to obtain a mixed monomer;
[0035] (3) Take 2.4 parts of ammonium persulfate in a container and add deionized water to dissolve to obtain an initiator solution
[0036] (4) Add 0.12 parts of sodium bicarbonate to a four-necked flask equipped with a stirrer, a thermometer, and a reflux condenser, add deionized water to dissolve, add the emulsifier solution obtained in step (1) and the mixed monomer obtained in step (2), stir at 300 r / min for 15 min, and obtain a pre-emulsion, heat to 75° C., add dropwise the initiator solution obtained in step (3), and react for 4 h, cool to 45° C., add 30% by mass of ammonia water to adjust the pH to 7.6, and obtain a polyacrylate emulsion;
[0037] (5) taking 120 parts of solid bisphenol A epoxy resin, heating at 80° C. for 25 min, adding 15 parts of nonylphenol polyoxyethylene ether and 4 parts of n-butanol, stirring at 350 r / min for 15 min, then increasing the speed to 1300 r / min for 1 h, and ultrasonically dispersing to obtain an epoxy resin emulsion;
[0038] (6) taking 90 parts of the epoxy resin emulsion obtained in step (5) and 120 parts of the polyacrylate emulsion obtained in step (3), mixing, stirring, and vacuum degassing to obtain an epoxy resin modified polyacrylate emulsion;
[0039] (7) Weigh 100 parts of ethyl orthosilicate and 200 parts of ethanol in a container, stir, add deionized water to dissolve, keep the temperature in a water bath at 75° C., add 1 part of 0.1M hydrochloric acid as a catalyst and 3 parts of an organic silane coupling agent KH-570, continue to stir and mix evenly, condense and reflux for 3 hours to obtain a uniform nano-silica sol;
[0040] (8) 40 parts of the nano-silica sol obtained in step (7) were placed in a magnetic stirrer, and 15 parts of nano-magnesium hydroxide were divided into three groups and added to the nano-silica sol once every 10 minutes at 25° C., 1200 r / min, 1 h to obtain nano-magnesium hydroxide modified silica sol;
[0041] (9) Take 15 parts of o-hydroxybenzaldehyde and 18 parts of acrylic acid in a container, add dichloromethane to dissolve, add 3 parts of dodecyl sulfuric acid and 15 parts of n-hexane, mix well, stir and react at 25° C. for 10 hours to obtain an intermediate;
[0042] (10) The intermediate obtained in step (9) was mixed with 8 parts of p-phenylenediamine, dissolved in methanol, stirred for reaction for 3 h, filtered and washed, and dried at 55 °C for 8 h to obtain a cross-linking agent containing a dual dynamic imine bond;
[0043] (11) Add 120 parts of the epoxy resin modified polyacrylate emulsion obtained in step (6) and 90 parts of the nano magnesium hydroxide modified silica sol obtained in step (8) into a container, stir at 25° C., 600 r / min, 1.5 h, mix well, then add 12 parts of the cross-linking agent obtained in step (10), 1 part of sodium dodecyl sulfate, 0.2 parts of BYK306, and 1 part of sodium polyacrylate, continue stirring for 2 h, and mix well to obtain a fire-retardant and corrosion-resistant water-based coating.
[0044] Example 2
[0045] (1) adding 0.40 parts of sodium lauryl sulfate and 0.60 parts of nonylphenol polyoxyethylene ether into a container, dissolving them with deionized water, and stirring them uniformly to obtain an emulsifier solution;
[0046] (2) 220 parts of methyl methacrylate, 100 parts of 2-ethyl acrylate, 110 parts of butyl acrylate, 12 parts of acrylic acid, and 35 parts of acrylonitrile were mixed in a container to obtain a mixed monomer;
[0047] (3) Take 3 parts of ammonium persulfate in a container and add deionized water to dissolve to obtain an initiator solution
[0048] (4) Add 0.15 parts of sodium bicarbonate to a four-necked flask equipped with a stirrer, a thermometer, and a reflux condenser, add deionized water to dissolve, add the emulsifier solution obtained in step (1) and the mixed monomer obtained in step (2), stir at 350 r / min for 15 min to obtain a pre-emulsion, heat to 80° C., add dropwise the initiator solution obtained in step (3), react for 5 h, cool to 50° C., add 30% by mass of ammonia water to adjust the pH to 8.0, and obtain a polyacrylate emulsion;
[0049] (5) taking 150 parts of solid bisphenol A epoxy resin, heating at 80° C. for 25 min, adding 20 parts of nonylphenol polyoxyethylene ether and 5 parts of n-butanol, stirring at 400 r / min for 15 min, then increasing the speed to 1500 r / min for 1 h, and performing ultrasonic dispersion to obtain an epoxy resin emulsion;
[0050] (6) taking 120 parts of the epoxy resin emulsion obtained in step (5) and 150 parts of the polyacrylate emulsion obtained in step (3), mixing, stirring, and vacuum degassing to obtain an epoxy resin modified polyacrylate emulsion;
[0051] (7) Weigh 120 parts of ethyl orthosilicate and 220 parts of ethanol into a container, stir, add deionized water to dissolve, keep the temperature in a water bath at 80° C., add 2 parts of 0.1M hydrochloric acid as a catalyst and 5 parts of an organic silane coupling agent KH-570, continue to stir and mix evenly, condense and reflux for 3 hours to obtain a uniform nano-silica sol;
[0052] (8) 60 parts of the nano-silica sol obtained in step (7) were placed in a magnetic stirrer, and 20 parts of nano-magnesium hydroxide were divided into three groups and added to the nano-silica sol once every 10 minutes at 25° C., 1200 r / min, 1 h to obtain nano-magnesium hydroxide modified silica sol;
[0053] (9) Take 18 parts of o-hydroxybenzaldehyde and 24 parts of acrylic acid in a container, add dichloromethane to dissolve, add 5 parts of dodecyl sulfuric acid and 18 parts of n-hexane, mix well, stir and react at 25° C. for 12 hours to obtain an intermediate;
[0054] (10) The intermediate obtained in step (9) was mixed with 10 parts of p-phenylenediamine, dissolved in methanol, stirred for reaction for 3 hours, filtered and washed, and dried at 60° C. for 10 hours to obtain a cross-linking agent containing a dual dynamic imine bond;
[0055] (11) Add 150 parts of the epoxy resin modified polyacrylate emulsion obtained in step (6) and 120 parts of the nano magnesium hydroxide modified silica sol obtained in step (8) into a container, stir at 25°C, 600 r / min, 1.5 hours, mix well, then add 15 parts of the cross-linking agent obtained in step (10), 1.5 parts of sodium dodecyl sulfate, 0.3 parts of BYK306, and 1.5 parts of sodium polyacrylate, continue stirring for 2 hours, and mix well to obtain a fire-retardant and corrosion-resistant water-based coating.
[0056] Example 3
[0057] (1) adding 0.30 parts of sodium lauryl sulfate and 0.45 parts of nonylphenol polyoxyethylene ether into a container, dissolving them with deionized water, and stirring them uniformly to obtain an emulsifier solution;
[0058] (2) taking 180 parts of methyl methacrylate, 80 parts of 2-ethyl acrylate, 90 parts of butyl acrylate, 8 parts of acrylic acid, and 25 parts of acrylonitrile in a container and mixing them uniformly to obtain a mixed monomer;
[0059] (3) Take 1.2 parts of ammonium persulfate in a container and add deionized water to dissolve to obtain an initiator solution
[0060] (4) Add 0.1 part of sodium bicarbonate to a four-necked flask equipped with a stirrer, a thermometer, and a reflux condenser, add deionized water to dissolve, add the emulsifier solution obtained in step (1) and the mixed monomer obtained in step (2), stir at 250 r / min for 15 min to obtain a pre-emulsion, heat to 70° C., add dropwise the initiator solution obtained in step (3), react for 3 h, cool to 40° C., add 30% by mass of ammonia water to adjust the pH to 7.2, and obtain a polyacrylate emulsion;
[0061] (5) Take 100 parts of solid bisphenol A epoxy resin, heat at 80° C. for 25 min, add 10 parts of nonylphenol polyoxyethylene ether and 3 parts of n-butanol, stir at 300 r / min for 15 min, then increase the speed to 1100 r / min for 1 h, and disperse by ultrasonication to obtain an epoxy resin emulsion;
[0062] (6) taking 60 parts of the epoxy resin emulsion obtained in step (5) and 100 parts of the polyacrylate emulsion obtained in step (3), mixing, stirring, and vacuum degassing to obtain an epoxy resin-modified polyacrylate emulsion;
[0063] (7) Weigh 90 parts of ethyl orthosilicate and 180 parts of ethanol into a container, stir, add deionized water to dissolve, keep the water bath at 70° C., add 1 part of 0.1M hydrochloric acid as a catalyst and 1 part of an organic silane coupling agent KH-570, continue to stir and mix evenly, condense and reflux for 3 hours to obtain a uniform nano-silica sol;
[0064] (8) taking 30 parts of the nano-silica sol obtained in step (7) and placing them in a magnetic stirrer, adding 12 parts of nano-magnesium hydroxide in three groups in batches, once every 10 minutes, to the nano-silica sol at 25° C., 1200 r / min, for 1 hour to obtain nano-magnesium hydroxide modified silica sol;
[0065] (9) Take 12 parts of o-hydroxybenzaldehyde and 16 parts of acrylic acid in a container, add dichloromethane to dissolve, add 2 parts of dodecyl sulfuric acid and 10 parts of n-hexane, mix well, stir and react at 25° C. for 8 hours to obtain an intermediate;
[0066] (10) The intermediate obtained in step (9) was mixed with 6 parts of p-phenylenediamine, dissolved in methanol, stirred for reaction for 3 hours, filtered and washed, and dried at 50° C. for 8 hours to obtain a cross-linking agent containing a dual dynamic imine bond;
[0067] (11) Add 100 parts of the epoxy resin modified polyacrylate emulsion obtained in step (6) and 60 parts of the nano magnesium hydroxide modified silica sol obtained in step (8) into a container, stir at 25° C., 600 r / min, 1.5 h, mix well, then add 8 parts of the cross-linking agent obtained in step (10), 0.8 parts of sodium dodecyl sulfate, 0.1 parts of BYK306, and 0.8 parts of sodium polyacrylate, continue stirring for 2 h, and mix well to obtain a fire-retardant and corrosion-resistant water-based coating.
[0068] Comparative Example 1
[0069] The difference between Comparative Example 1 and Example 1 is that steps (5) and (6) are deleted, and step (11) is changed to adding 120 parts of polyacrylate emulsion and 90 parts of nano-magnesium hydroxide modified silica sol obtained in step (8) into a container, mixing at 25° C., 600 r / min, 1.5 h, and then adding 12 parts of the cross-linking agent obtained in step (10), 1 part of sodium dodecyl sulfate, 0.2 parts of BYK306, and 1 part of sodium polyacrylate, and continuing to stir for 2 h. Mixing evenly obtains a fire-retardant and corrosion-resistant water-based coating; the remaining steps are the same as in Example 1.
[0070] Comparative Example 2
[0071] The difference between Comparative Example 2 and Example 1 is that the film-forming emulsion is replaced with a commercially available polyurethane emulsion; the remaining steps are the same as those of Example 1.
[0072] Comparative Example 3
[0073] The difference between Comparative Example 3 and Example 1 is that steps (7) and (8) are deleted, and step (11) is changed to adding 120 parts of the epoxy resin modified polyacrylate emulsion obtained in step (6) and 15 parts of nano-silicon dioxide into a container, mixing them uniformly at 25° C., 600 r / min, 1.5 h, and then adding 12 parts of the cross-linking agent obtained in step (10), 1 part of sodium dodecyl sulfate, 0.2 parts of BYK306, and 1 part of sodium polyacrylate, and continuing to stir for 2 h. Mixing uniformly obtains a fire-retardant and corrosion-resistant water-based coating; the remaining steps are the same as those in Example 1.
[0074] Comparative Example 4
[0075] The difference between Comparative Example 4 and Example 1 is that in step (8), step (8) is changed to taking 60 parts of the nano-silica sol obtained in step (7) into a magnetic stirrer, and adding 15 parts of nano-titanium dioxide in batches into three groups, once every 10 minutes, to the nano-silica sol at 25°C, 1200 r / min, 1 hour to obtain nano-titanium dioxide modified silica sol; the remaining steps are the same as in Example 1.
[0076] Comparative Example 5
[0077] The difference between Comparative Example 5 and Example 1 is that in step (8), step (8) is changed to taking 60 parts of the nano-silica sol obtained in step (7) in a magnetic stirrer, and adding 15 parts of nano-aluminum hydroxide in batches into three groups, once every 10 minutes, to the nano-silica sol at 25°C, 1200 r / min, 1 hour to obtain nano-aluminum hydroxide modified silica sol; the remaining steps are the same as in Example 1.
[0078] Comparative Example 6
[0079] The difference between Comparative Example 6 and Example 1 is that steps (9) and (10) are deleted, and step (11) is changed to adding 120 parts of the epoxy resin modified polyacrylate emulsion obtained in step (6) and 90 parts of the nano magnesium hydroxide modified silica sol obtained in step (8) into a container, mixing them evenly at 25° C., 600 r / min, 1.5 h, and then adding 12 parts of the isocyanate crosslinking agent toluene diisocyanate purchased on the market, 1 part of sodium dodecyl sulfate, 0.2 parts of BYK306, and 1 part of sodium polyacrylate, and continuing to stir for 2 h. Mixing evenly obtains a fire-retardant and corrosion-resistant water-based coating; the remaining steps are the same as those in Example 1.
[0080] Comparative Example 7
[0081] The difference between Comparative Example 7 and Example 1 is that steps (9) and (10) are deleted, and step (11) is changed to adding 120 parts of the epoxy resin modified polyacrylate emulsion obtained in step (6) and 90 parts of the nano magnesium hydroxide modified silica sol obtained in step (8) into a container, mixing them uniformly at 25° C., 600 r / min, 1.5 h, and then adding 12 parts of a commercially available disulfide bond-containing cross-linking agent N-hydroxysuccinimide-disulfide-N-hydroxysuccinimide, 1 part of sodium dodecyl sulfate, 0.2 parts of BYK306, and 1 part of sodium polyacrylate, and continuing stirring for 2 h. Mixing uniformly obtains a fire-retardant and corrosion-resistant water-based coating; the remaining steps are the same as in Example 1.
[0082] Effect example
[0083] Table 1 below shows the performance analysis results of the fire-retardant and corrosion-resistant water-based coatings of Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.
[0084] Table 1
[0085]
[0086]
[0087]
[0088] From the data comparison of the embodiment and the comparative example, it can be found that the present invention uses epoxy resin modified polyacrylate emulsion as a film-forming emulsion. The acrylic emulsion contains a molecular chain structure formed by polymerization of acrylic ester monomers, which gives the coating good flexibility and initial adhesion. The ester group and other groups on the molecular chain help maintain the basic physical properties of the coating. The epoxy resin is used for modification, and the epoxy group reacts with the curing agent to form an interpenetrating network structure with the polyacrylate emulsion, thereby improving the density of the coating; the epoxy group and the benzene ring structure can effectively resist the erosion of corrosive media such as acids and alkalis, and prevent the penetration of corrosive ions by forming a dense protective layer. Improve the corrosion resistance of the coating; magnesium hydroxide modified silica sol composite epoxy resin modified polyacrylate emulsion is used as a film-forming material. When the coating forms a film, the polymer molecules in the polyacrylate emulsion gradually form a continuous membrane structure through the entanglement and interaction of molecular chains. The silica particles in the silica sol are evenly dispersed in the emulsion system. As it dries and forms, the silica particles will gradually aggregate and fill the gaps between the polyacrylate molecular chains. The surface silicon hydroxyl groups interact with the active groups of the polyacrylic acid molecular chains, and are connected by hydrogen bonds or silicon-oxygen bonds. The synergistic effect forms a dense and uniform three-dimensional network structure, thereby improving the physical properties of the coating. The present invention uses a cross-linking agent containing a double dynamic imine bond, which undergoes a cross-linking reaction with the active groups on the polyacrylate molecular chain to form a more stable and complex three-dimensional network structure, thereby enhancing the integrity and density of the coating. At the same time, when the coating is damaged by external force, the imine bond breaks, and the molecular chains around the damaged area can be rearranged and cross-linked under certain conditions to achieve self-repair. The flexibility and fluidity of the polyacrylate emulsion provide a basis for the rearrangement of the molecular chains, while the rigid structure of the silica sol helps to maintain the shape and stability after repair, so that the repaired coating can be restored to performance close to the original state, thereby improving the service life and sustainability of the coating.
[0089] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive from any point of view, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and no mark in the claims should be regarded as limiting the claims involved.
Claims
1. A method for preparing a fire-resistant and corrosion-resistant water-based coating, characterized in that: The method comprises the following preparation steps: (1) preparing an emulsifier solution; (2) taking methyl methacrylate, 2-ethyl acrylate, butyl acrylate, acrylic acid, and acrylonitrile in proportion and mixing them uniformly to obtain a mixed monomer; (3) adding a pH buffer into a container, adding the emulsifier solution obtained in step (1) and the mixed monomer obtained in step (2), stirring evenly to obtain a pre-emulsified liquid, heating, adding dropwise an initiator solution, and adjusting the pH after the reaction is complete to obtain a polyacrylate emulsion; (4) taking the epoxy resin emulsion, mixing it with the polyacrylate emulsion obtained in step (3), stirring it, and performing a degassing treatment to obtain an epoxy resin modified polyacrylate emulsion; (5) Weighing ethyl orthosilicate and ethanol in a container according to the mass ratio, stirring, adding deionized water to dissolve, keeping the temperature in a water bath, adding a catalyst and an organic silane coupling agent, continuously stirring and mixing, condensing and refluxing, and obtaining a uniform silica sol; (6) adding nano magnesium hydroxide to the nano silica sol obtained in step (5), stirring and dispersing, to obtain nano magnesium hydroxide modified silica sol; (7) adding the polyacrylate emulsion obtained in step (3) and the nano-magnesium hydroxide-modified silica sol obtained in step (6) into a container, adding a crosslinking agent, heating and stirring, continuing to add an emulsifier, a defoaming agent, and a thickener, and mixing evenly to obtain a fire-resistant and corrosion-resistant water-based coating; The cross-linking agent is prepared by the following method: (i) taking o-hydroxybenzaldehyde and an alcohol compound into a container, adding an organic solvent to dissolve, adding a catalyst and a water absorbent, mixing evenly, and reacting to obtain an intermediate; (ii) mixing the intermediate obtained in step (i) with p-phenylenediamine to react to obtain a cross-linking agent containing a dual dynamic imine bond; The molar mass ratio of o-hydroxybenzaldehyde, alcohol compound, catalyst and water absorbent in step (i) is 1.1-1.8:1.1-1.5:0.4-0.6:1.5-2.5; the molar mass ratio of intermediate and p-phenylenediamine in step (ii) is 0.25-0.6:1-1.
2.
2. The method for preparing a fire-resistant and corrosion-resistant water-based coating according to claim 1, characterized in that: The emulsifier in step (1) is sodium dodecyl sulfate and nonylphenol polyoxyethylene ether, and the mass ratio thereof is 1:1.5-2.
3. The method for preparing a fire-resistant and corrosion-resistant water-based coating according to claim 1, characterized in that: In the step (2), the mass ratio of methyl methacrylate, 2-ethyl acrylate, butyl acrylate, acrylic acid and acrylonitrile is 180-220:80-100:90-110:8-12:25-35.
4. The method for preparing a fire-resistant and corrosion-resistant water-based coating according to claim 1, characterized in that: The pH buffer in step (3) is sodium bicarbonate, the mass of which is 0.1-0.5% of the total monomer mass in step (2); and the initiator is ammonium persulfate, the mass of which is 0.2-1% of the total monomer mass in step (2).
5. The method for preparing a fire-resistant and corrosion-resistant water-based coating according to claim 1, characterized in that: The epoxy resin emulsion in step (4) is a bisphenol A epoxy resin emulsion with an epoxy equivalent of 180 to 190 g / eq; the epoxy resin emulsion is obtained by reacting bisphenol A epoxy resin, a hydrophilic monomer, an initiator and an emulsifier.
6. A fire-resistant and corrosion-resistant water-based coating, characterized in that: The fireproof and corrosion-resistant water-based paint comprises the following components: 100-150 parts of polyacrylate emulsion, 60-100 parts of epoxy resin emulsion, 30-50 parts of silica sol, 10-25 parts of nano magnesium hydroxide, 6-15 parts of cross-linking agent, 0.3-2 parts of emulsifier, 0.5-2 parts of thickener and 0.1-0.3 parts of defoaming agent; the fireproof and corrosion-resistant water-based paint is prepared by the preparation method described in any one of claims 1 to 5.
Citation Information
Patent Citations
Preparation method of polyacrylate / nano silicon dioxide composite emulsion coating material
CN105273556A
Preparation method of composite waterproof coating for tunnel
CN110790549A
Cross-linking agent containing double dynamic imine bonds, self-repairing polymer and preparation method of self-repairing polymer
CN113512023A
Preparation method of modified acrylate emulsion
CN117069898A
Fireproof water-based paint for interior and exterior walls and preparation method of fireproof water-based paint
CN118995004A